Efektifitas Penggunaan Aplikasi Canva Sebagai Media Pembelajaran Masa Kini Di Era 4.0 - Rosalinda, Rosalinda; Munajjah, Cut Farah; Ikhwani, Yudi (Jurnal Sosial Humaniora Sigli, 2023)
Challenges faced by Arabic language learners due to the development of increasingly sophisticated digital technology include the need to remain innovative and creative in creating interesting learning materials, one of which is digital media. The aim of this research is to find out how useful the Canva application is as a tool/medium for learning modern Arabic. The research method used by researchers is a field research method with a qualitative research approach. The approach used in this research is a qualitative approach by carrying out objective observations and analysis through collecting data and conclusions as well as explaining several facts found in the field. The findings in the field include: a. Using the Canva application to learn Arabic has succeeded in attracting students' interest and enthusiasm in learning Arabic; b. Using the Canva application to learn Arabic makes it very easy for lecturers to communicate concepts/material and provide feedback; c. Using this app to learn Arabic can improve students' writing skills in an easy, fun, and accessible way. Keywords : Effectiveness, Arabic Language Learning, Canva Application